Spatial differentiation of the population ageing process in lodzkie voivodeship - Majdzińska, Anna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The main aim of this paper is the analysis of the changes in lodzkie voivodeship population structure with the focus on the population ageing process. The research was conducted at the beginning of the first and second decade of the 21st century and in the near future for poviats and gminas. In addition, to indicate the broader context of the developments in this regard, the analyses for this voivodeship were carried out for the years 1995-2003. The current situation was presented against the population age structure of other Polish regions.